PRAKTIK BANK THITHIL DAN IMPLIKASINYA MENURUT PANDANGAN MASYARAKAT MUSLIM WILAYAH PERKAMPUNGAN BETHEK KOTA MALANG - Saputra, Arnanda Aji; Multifiah, Multifiah (Fakultas Ekonomi, UIN Maliki Malang, 2013)
The present study aimed at finding out various practices of Bank Thithil at Bethek Urban Village, Malang, along with the people’s perception and the impact of such practices towards the people’s welfare. Employing qualitative approach, this study focuses on the people’s perception, particularly those belonging to debtors trapped in Bank Thithil, such bank’s creditors, and some local cultural leaders, who lived at Bethek Urban Village, Malang. Data collection was carried out by interviews, observation and documentation. In analyzing the data, Miles Huberman’s analysis was employed which consisted of the following action: collection, reduction, display, and conclusion drawing supported by a phenomenological method which tried to capture and understand the reality. The result showed that Bank Thithil at Bethek Urban Village belonged to an informal financial organization as it was not a legal entity. As a consequence, the creditors may set rules of loan and sanctions without any reference to the legal law of financial organizations in Indonesia. The people’s perception towards Bank Thithil was various; some people felt fine with its practices because they need it and some another people strongly disagreed for some reasons, one is the prohibition on Islamic law.